Chitosan patterning on titanium implants - Gilabert-Chirivella, Eduardo (2017)
The purpose of this study is to develop new implant surfaces in which polymeric domains with antibacterial properties can alternate with titanium domains and to determine the cell behaviour on the substrates. Surface microgrooves with a separation of 60 μm between them were performed on pure titanium disks using a modified 3D printer. Shavings were removed after the process. These were then coated with an antibacterial polysaccharide (chitosan) and mouse C2C12 myoblast and MC3T3-E1 pre-osteoblast were cultured on the hybrid substrates to determine cell adhesion. Surface geometries were determined using optical microscopy. Functionalized (F) and unfuctionalized (NF) substrates were characterized using field emission scanning electron microscopy (FESEM) and water contact angle. Stability of the coating in water was also investigated. FESEM images showed surface microgrooves with a micro-topography on the ridges between them. It was observed the entire surface covered with a thin coating of chitosan which followed the surface features. MC3T3-E1 pre-osteoblasts preferentially adhered on the titanium regions whereas C2C12 myoblasts distributed uniformly throughout the whole surface.